2017
DOI: 10.1038/s41598-017-03894-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of olfactory nerve damage measured with thallium-based olfactory imaging in patients with idiopathic olfactory dysfunction

Abstract: Idiopathic olfactory disorder is resistant to treatment, and the recovery time is long. This study investigated the prognostic value of the migration of nasally administered thallium-201 to the olfactory bulb (thallium migration to the OB), a measure of olfactory nerve damage, in patients with idiopathic olfactory disorders. Twenty-four patients with idiopathic olfactory disorders were enrolled in the study (7 women and 17 men; aged 23–73 years). We retrospectively analyzed potential prognostic markers in subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…The OB volume was significantly larger in the parosmia group than in the parosmia and hyposmia group (Fig. , p = 0.029); however, the mean OB volume in both groups (31.2 mm 3 in the parosmia group and 22.6 mm 3 in the parosmia and hyposmia group) was lower than the normal value in healthy subjects (≥58 mm 3 for <45 years; ≥46 mm 3 for older subjects). The nasal thallium uptake ratio in the olfactory cleft was significantly correlated with T&T odor recognition thresholds (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The OB volume was significantly larger in the parosmia group than in the parosmia and hyposmia group (Fig. , p = 0.029); however, the mean OB volume in both groups (31.2 mm 3 in the parosmia group and 22.6 mm 3 in the parosmia and hyposmia group) was lower than the normal value in healthy subjects (≥58 mm 3 for <45 years; ≥46 mm 3 for older subjects). The nasal thallium uptake ratio in the olfactory cleft was significantly correlated with T&T odor recognition thresholds (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…In Japan, T&T olfactometry (Daiichi Yakuhin Sangyo, Tokyo, Japan) is a standard technique for estimating the olfactory thresholds; the normal odor recognition threshold score of each nostril is ≤2.0. The olfactory severities were categorized according to the mean T&T recognition thresholds, and the patients were diagnosed with anosmia when the T&T recognition thresholds were ≥5.6 . Each odorant was dissolved in mineral oil to form a graded series of concentrations and was then applied liberally on blotting papers followed by presentation to the patients using T&T olfactometry.…”
Section: Methodsmentioning
confidence: 99%
“…With the use of in vivo imaging via SPECT-CT, we demonstrated that thallium-201 migration to the axon terminals of olfactory sensory neurons was increased under reduced inhibitory input from damaged olfactory bulb interneurons, following nasal administration of rotenone in rats. Decreased thallium-201 migration rate to the olfactory bulb predicted a poorer prognosis for patients with idiopathic olfactory dysfunction [23]. Patients with idiopathic olfactory dysfunction and decreased thallium-201 migration rate to the olfactory bulb may be at high risk for pre-symptomatic idiopathic Parkinson's disease because the overexpression of dopaminergic interneurons in the olfactory bulbs of patients diagnosed with idiopathic Parkinson's disease has been demonstrated [24].…”
Section: Discussionmentioning
confidence: 99%
“…(2022) Higher migration rates to the OB were found in subjects with normal olfactory thresholds compared to patients with impaired olfaction because the tracer migration was associated with intact olfactory nerve fibers. Although these studies do not report on the use of imaging, and specifically PET imaging, as a tool for the evaluation of the PK properties of IN dosage forms, they support the feasibility and tolerability of human imaging after IN administration of radiotracers and suggest the direct role of the olfactory neurons in the transfer of materials within the nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%